Scientific Religious Surnames and their Implications in the Arab Islamic Society - Abdul Sattar M. D; Abdul Karim M. Abed (مجلة جامعة الأنبار للعلوم الإنسانية, 2021)
Addressing scientific religious surnames and their implications in the Arab Islamic society is considered an important step that emphasizes the association of the scholar to his community. Through surnames, we were able to know scholars in various fields of specialization, the scientific or the humanitarian, because most of the important scientific figures in the society are known for their surnames as a kind of pride to be affiliated to sciences they excelled in, such as Al-Faqeeh (philologist) and Al-Hafidh (memorizing the Holy Quran) among others. Moreover, they became inseparable from the scholars in accordance to the cultural development of the Arab Islamic society, especially the Abbasid Era (132 AH - 656AD).